Biology of Sturmia convergens (Dipteara:Tachinidae) para sitizing monarch butterfly, Danaus chrysippus damaging Akanda (Calotropis gigantean ) in Bangladesh (The Journal of Plant Protection Sciences, 2024)
Sturmia convergens (Wiedemann) is an  endoparasite of the monarch butterfly,  Danaus chrysippus (L.) larvae which feeds on  the leaves of an indigenous medicinal plant  ferent parts of Bangladesh. This was recorded  as a akanda (Calotropis gigantea) abundantly  grown in diftachinid endoparasite of the monarch butterfly, Danaus chrysippus larvae (2).  Parasitism of pine pests Diprion pini L. and  D. sertifer by a tachinid, S. inconspicua has been reported in west Slovakia (6). Shapiro (7) described that S. scutellata parasitized caterpillars of gypsy moth. The parasitism of lepidopterans by the tachinid insects i.e. S. bella and S. vanessae has also been enumer ated by several authors (3,5, 1). The biology of this promising tachinid parasite has not yet been reported and described in Bangladesh. Therefore, some observations on the biology of S. convergens and its possible role as bio control has been invested. The parsitized D.
Keywords: development; Calotropis gigantea; convergens was accom